DEVELOPING PEDAGOGICAL REFLECTION IN STUDENTS THROUGH INDEPENDENT LEARNING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article analyzes the role of the independent learning process in the development of pedagogical reflection in students. It is shown that the effective organization of independent learning directs students to activity, critical thinking, self-assessment and professional development. It also highlights the extent to which the student's knowledge, skills and competencies are formed in the process of reflection and the importance of pedagogical support in this process. The results of the study confirm that independent learning and pedagogical reflection are closely related, and one creates the necessary conditions for the development of the other.